login
a(n) = a(n-1)*a(n-2)*a(n-3)*(1+1/(n-3)), a(1)=a(2)=a(3)=1.
0

%I #10 Aug 27 2024 21:45:13

%S 1,1,1,2,3,8,60,1728,967680,114661785600,215698302044209152000,

%T 26592225368515593301597083402240000000,

%U 723457119656730571214801208759677424070060705650559470796800000000000

%N a(n) = a(n-1)*a(n-2)*a(n-3)*(1+1/(n-3)), a(1)=a(2)=a(3)=1.

%t a[1] = a[2] = a[3] = 1; a[n_] := a[n - 1]*a[n - 2]*a[n - 3]*(1 + 1/(n - 3)); Table[ a[n], {n, 1, 13}]

%K easy,nonn

%O 1,4

%A _Benoit Cloitre_, Jul 29 2002

%E Edited by _Robert G. Wilson v_, Jul 31 2002

%E a(11) corrected by _Sean A. Irvine_, Aug 27 2024